Enhanced electrochemical activity of ternary Co-Mn-Zn oxide for the fabrication of hybrid supercapacitor applications. (10th December 2022) - Suganya, S.; Maheshwaran, G.; Ramesh Prabhu, M.; Devendran, P.; Krishna Kumar, M.; Sudhahar, S.
Abstract: The investigations of ternary nanocomposite electrode based materials have been extensively studied for high-performance energy conversion/storage applications due to its large surface area, multivalent cations, and high stability with good electrical conductivity. Here, the ternary Co-Mn-Zn Oxide nanocomposite has been prepared by a facile and cost-effective hydrothermal approach. The synthesized materials were analyzed with various analytical tools to confirm structural, morphological, and elemental studies. The cyclic voltammetry (CV) analysis of Co-Mn-Zn Oxide nanocomposite manifests a high specific capacitance (Cs1 ) of 675.3 F/g at the scan rate of 10 mV/s. Electrochemical impedance spectroscopy (EIS) analysis exhibits the solution resistance (Rs ) and charge-transfer resistance (Rct ) of 0.44 Ω and 0.58 Ω. The galvanostatic charge-discharge (GCD) study shows a long charge/discharge time and better redox activities of the prepared ternary nanocomposite. The ternary Co-Mn-Zn Oxide nanocomposite reveals the coulombic efficiency of 100.6 % and capacitive retention of 94.5 % for 3000 charge-discharge cycles. Moreover, the Co-Mn-Zn Oxide//AC hybrid supercapacitor (HSC) device demonstrates a high energy density of 12.06 Wh/kg, a high power density of 3249.5 W/kg, Coulombic efficiency of 101.2 %, and good capacitive retention of 68.9 % for 2000 cycles. Graphical abstract: Unlabelled Image Highlights: Co-Mn-Zn Oxide ternary nanocomposite was synthesized by one-pot hydrothermal method. Co-Mn-Zn Oxide nanocomposite delivers the specific capacitance of 675.3 F/g at 10 mV/s. The HSC device delivers the high energy density of 12.06 Wh/kg and high power density of 3249.5 W/kg. The HSC device demonstrated capacitive retention of 68.9 % and coulombic efficiency of 101.2 % after 2000 cycles.